Motivasi Belajar dengan Kemandirian Belajar pada Siwa Sekolah Menengah Pertama - Manta, Dedy Ardito Putra; Arifiana, Isrida Yul; Efendy, Mamang (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to determine the relationship between learning motivation and learning independence in junior high school students. This research is a type of quantitative research. The population in this study was 800 students at Smpn 33 Surabaya. The sample in the study amounted to 260 students with the sampling technique using the Accidental Sampling Technique. This research instrument uses a learning motivation scale with aspects proposed by Sardiman (2013) and a learning independence scale with aspects proposed by Song & Hill (2007). The data analysis method in this research uses Person Correlation Product Moment with the help of IBM SPSS for Windows. The results of the correlation analysis between learning motivation and learning independence produce significant values, meaning that there is a significant positive relationship between learning motivation and learning independence in junior high school students. where the higher the learning motivation, the higher the learning independence in junior high school students, and conversely the lower the learning motivation, the lower the learning independence in junior high school students. This means that the hypothesis proposed in this research is accepted. The implications of this research show that increasing learning motivation is the foundation for building learning independence in junior high school students.